Implementasi Metode Analytical Hierarchy Process (AHP) Dalam Perancangan Matriks Penilaian Kinerja (Studi Kasus Pada PT.Perkebunan Nusantara VI Unit Usaha Kayu Aro Kerinci) - Nur Angraini; Imam Bayhaqi; Erna Rahayu Eko Wiriani (LPPM Politeknik Jambi, 2021)
PT. Perkebunan Nusantara VI Timber Business Unit Aro Kerinci is a company engaged in processing. Customer satisfaction is a major key in the service development process. Therefore, increasing the performance of a company is to increase the quality of a company. Performance is a description of the level of implementation of an activity, program, realizing the goals, objectives, mission and vision of the organization which are contained in the formulation of an organization's strategic scheme (strategic planning). Retrieval of performance results at PT. Perkebunan Nusantara VI Aro Kerinci Timber Business Unit has four perspectives and ten indicators, namely financial indicators with increasing profit perspective, customer indicators, consumer loyalty and increasing number of consumers, internal business indicators, number perspective, work accident rate and employee attendance and learning perspective and satisfaction indicators growth. employees, increase employee competition and rewards or rewards. To determine the level of service at PT. Perkebunan Nusantara VI Aro Kerinci Timber Business Unit is carried out using the Analytical Hierarchy Process (AHP) method with hierarchical stages, pair comparisons and consistency checks in carrying out this consistency check carried out by several stages of Weight Sum Factor (WSF), Consistency Factor (CF), index consistency (CI), index ratio (RI) and Consistency Ratio (CR).